Perlindungan Kebebasan Berpendapat Dalam Media Sosial dalam Perspektif Ham - Nikmah, Putri Fithrotin (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The Unitary State of the Republic of Indonesia is a legal state based on Pancasila Democracy. Democracy itself, which is a system of government in Indonesia, has implications for equal rights and responsibilities and equal treatment for all its citizens. Every citizen is free to express his opinion in accordance with article 28E paragraph 3 of the 1945 Constitution. With today's sophisticated technology, Indonesian citizens express their opinions on existing social media networks. And in terms of freedom of expression on social media, there needs to be protection to protect against the impact of this.